2021
DOI: 10.1159/000511761
|View full text |Cite
|
Sign up to set email alerts
|

Enteroendocrine Dysfunction in Two Saudi Sisters

Abstract: Proprotein convertase (PC) deficiency is a rare autosomal recessive disorder caused by mutations in proprotein convertase subtilisin/kexin type 1 (PCSK1). It is characterized by severe malabsorptive early-onset diarrhea, obesity, and systemic endocrinopathies. Only few cases have been reported in the literature; we have add two female sisters with some difference in clinical progress. Herein, we describe two sisters with congenital osmotic diarrhea diagnosed with PC1/3 deficiency, causing malabsorptive diarrhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The form and severity of hormonal insufficiency vary from patient to patient with PC1/3 deficiency. To date, there have been 32 cases of PCSK1 deficiency recorded so far, with patients presenting a varied range of symptoms (6,8,9). The first patient with a PCSK1 mutation was reported by O'Rahilly et al in 1995 (11); of total 33 patients diagnosed (including the one we reported) (see Table 2), all presented with malabsorptive diarrhea before the age of 3 years, 60.6% (20/33) in males and 39.4% (13/33) However, except for diarrhea, the three patients who all had the c.927C > G variant and the two patients who all had the c.1350_1353del (p. D451fs) mutation had little in common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The form and severity of hormonal insufficiency vary from patient to patient with PC1/3 deficiency. To date, there have been 32 cases of PCSK1 deficiency recorded so far, with patients presenting a varied range of symptoms (6,8,9). The first patient with a PCSK1 mutation was reported by O'Rahilly et al in 1995 (11); of total 33 patients diagnosed (including the one we reported) (see Table 2), all presented with malabsorptive diarrhea before the age of 3 years, 60.6% (20/33) in males and 39.4% (13/33) However, except for diarrhea, the three patients who all had the c.927C > G variant and the two patients who all had the c.1350_1353del (p. D451fs) mutation had little in common.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, 32 PC1/3 deficient patients have been reported in the literature. Among them, 28 (87.5%) patients had homozygous mutations and only 4 (12.5%) were compound heterozygotes (6)(7)(8)(9)(10). Depending on the location of the mutation site and the type of mutation, the impact on the final result of protein synthesis and enzyme activity frequently differs.…”
Section: Introductionmentioning
confidence: 99%
“…genes) [92]; celiac disease (CPED1 gene) [93]; hereditary spherocytosis type 3 (SPTA1 gene) [89]; developmental delay, cerebellar hypoplasia, and myoclonic seizures (KCNMA1 gene) [74]; Cenani-Lenz syndrome (APC gene) [74]; Sjogren-Larsson syndrome (ELOVL4 gene) [74]; autism spectrum disorder (multigene) [94]; congenital heart disease (PRKD1 gene) [95]; ciliopathies [96]; Parkinsonism (PLA2G6 gene) [97]; retinal dystrophies (CLRN1, ABCA4, CERKL, AGBL5, CDH16, and DNAJC17 genes) [98][99][100]; Pediatric Asthma [101]; cardiovascular genetic diseases (LDLR gene) [102]; enteroendocrine dysfunction (PCSK1) [103]; tricho-hepato-enteric syndrome (TTC37 and SKIV2L) [104]; Wolcott-Rallison syndrome (EIF2AK3) [105], Fanconi-Bickel syndrome (SLC2A2) [105] and Alström syndrome (Exon 19 Skipping in ALMS1 Gene) [106,107]; using whole exome or whole genome analysis revealed disease markers in Saudi population. Families with autosomal recessive retinal dystrophies from various ethnicity including Saudis were analysed for candidate genes using WES, 45 unique deleterious variants including 18 novel variants observed [108].…”
Section: Other Genetic Diseasesmentioning
confidence: 99%
“…Additional clinical case investigations have since led to the discovery of 34 more cases of congenital recessive PC1/3 deficiency, corresponding to 29 distinct PCSK1 variants ( Table 1 ). Cases up until 2019 [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ] are reviewed in a paper by Pépin et al [ 7 ]. Additional cases have since been reported [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cases up until 2019 [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ] are reviewed in a paper by Pépin et al [ 7 ]. Additional cases have since been reported [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. All patients carried either homozygous or compound heterozygous PCSK1 variants and suffered from severe early malabsorptive diarrhea (within the first three months of life), which was the main clinical feature driving subsequent genetic PCSK1 analysis.…”
Section: Introductionmentioning
confidence: 99%